PROFILING DAN BERBAGAI GAGASAN POLITIK KEPENTINGAN MASYARAKAT LOKAL DALAM IKLAN PEMILIHAN GUBERNUR JAWA TENGAH 2013 - Santosa, Hedi Pudjo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
In a political branding, there are various mechanisms by which local candidates profiling themselves and present a variety of political ideas associated with the interests of local communities. The values of the locality, the figure personality, distinctive local political sentiment of this can be traced in the local political advertising in Central Java Gubernatorial election in 2013.Which is usually appear in the equivalent combination of political sentiment and tagline